Outsourcing the enforcement of modern slavery: Overcoming the limitations of a market-based disclosure model. (April 2022) - Harris, Hannah; Nolan, Justine
Recent legislative efforts to address modern slavery emphasise corporate disclosure as the primary regulatory tool. New modern slavery disclosure laws harden the expectation that business will conduct itself responsibly; however, they are founded on a soft approach to enforcement which is essentially outsourced to the market. This paper questions the effectiveness of this disclosure-based enforcement mechanism, which primarily relies on a narrowly defined concept of 'the market' as the basis for its regulatory strategy. Drawing on comparisons with alternative legislative enforcement frameworks to counter foreign bribery and illegal logging, this paper highlights the opportunities and limitations of reliance on market forces for regulation and suggests a path forward for enhancing the modern slavery enforcement approach.